RESPONS FISIOLOGIS SAPI BALI TERHADAP PERUBAHAN CUACA DI KABUPATEN MERAUKE PAPUA - Heny Vensye Saiya (AGRICOLA, 2014)
The objective of this study was to determine the physiological responses of bali cattle (Bos javanicus) in response to weather changes in Merauke district. The experiment was carried out in  Wasur Village II, Merauke district. Twelve bali cattle (age rangedbetween 2-5 years) were used in this study. Every morning during the study periode, animalswere removed from the cage and placed in the ranch and in the evening they sent back into the cage. Microclimate data were recorded around the research station where cattles were  located during 8 am until 4 pm, included dry bulb temperature, wet bulb temperature, wind speed, and solar radiation. Relative humidity (RH) and Temperature Humidity Index (THI) were also calculated. The physiological responses (rectal temperature, skin temerature, body temperature, respiration rate, and pulse rate) of  bali cattles were monitored every 21 days between April and May. Data were analyzed using the repeated measurement GLM procedure. Bali cattle in this study had a thermoregulatory ability.The different weather between west monsoon on April and east monsoon on May were showed that bali cattles were able to maintain the physiological responses during monsoon changed. Bali cattle were able to maintain their physiological responses within different weather condition, west monsoon on April and east monsoon on May.